AN ANALYSIS OF THE INFLUENCE OF FAMILY LANGUAGE-BASED PARENTING PATTERNS ON THE DEVELOPMENT OF RESPONSIBILITY CHARACTER AMONG ADOLESCENTS IN THE DIGITAL ERA - Muhammad Asriadi; Masni Masni; Asriati Asriati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the influence of family language-based parenting patterns on the development of responsibility character among adolescents in the digital era. A quantitative survey method was employed, involving 100 adolescent respondents residing in five regions of Makassar City: Jl. Galangan Kapal, Jl. Tinumbu, Jl. Kandea, Jl. Pampang Raya, and Jl. Abubakar Lambogo. The research instrument used was a closed-ended questionnaire measuring parental language-based parenting tendencies (democratic, authoritarian, and permissive) and adolescents' levels of responsibility character. The findings reveal that the democratic parenting pattern has the most significant impact on the development of responsibility, marked by open communication, logical explanation, and two-way dialogue. In contrast, authoritarian and permissive styles tend to be less effective in fostering adolescent responsibility. Pearson correlation tests showed a significant positive relationship between democratic language-based parenting and adolescent responsibility levels. This study emphasizes the crucial role of healthy family communication practices as a foundation for character education in adolescents, especially amidst the challenges of the digital age.